Side Effects of Using Virtual Reality Tools and Their Measurement - Cossio, Samantha; Magro, Gaia; Dentice, Sara; Chiappinotto, Stefania; Galazzi, Alessandro (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Virtual reality (VR) is becoming increasingly important in education, offering immersive learning experiences. However, head-mounted displays (HMDs) often cause side effects such as cybersickness and discomfort, which can affect learning outcomes. The study of side effects using validated tools is becoming increasingly important as it can influence the perceived quality of education. An overview of virtual reality and tools for measuring side effects can be a starting point for future research and suggests that the prevalence of VR sickness is still problematic and little is known about side effects, also making these issues a primary aim of future studies and considering not only students but also professionals involved in Virtual Reality Education.